PERBANDINGAN KEAKURATAN REKOMENDASI SAHAM PADA PT RHB SEKURITAS INDONESIA DAN PT MANDIRI SEKURITAS - Dira Meiliza; Said Musnadi (Departemen Manajemen, 2022)
This study aims to find the accuracy of stocks, target price and bias recommendation by analyzing PT RHB Sekuritas Indonesia and PT Mandiri Sekuritas. The data were collected from primary and secondary sources. Population of this study were all LQ 45 companies listed in Indonesia Stock Exchange that have been received recommendation from PT RHB securities Indonesia and PT Mandiri Sekuritas for the period of February- July 2020. The hypothesis testing used in this study by using Uji Beda t-test, the results show that: 1) The level of accuracy of PT RHB Sekuritas Indonesia analyst recommendations is more accurate than PT Mandiri Sekuritas.. 2) The target price for PT Mandiri Sekuritas analysis is superior to that of PT RHB Sekuritas Indonesia 3) Analysis recommendation of PT RHB Sekuritas and PT Mandiri Sekuritas shown bias negatively.